-Almost sure convergence for multivariate probability density estimate from dependent observations. Issue 3 (1st February 2017) - Badaoui, Mohammed; Rhomari, Noureddine
ABSTRACT: We study the almost sure convergence of integrated square error of the wavelet density estimators for multivariate absolutely regular observations. We state that these estimates reach, up to a logarithm, the optimal rate of -almost sure convergence for densities in the Sobolev space with s > 0. The support of f may be the whole space . Precisely, if fn is a such estimate of f, we prove that, a.s. Moreover, we give an estimate of the constant in this upper bound. Proofs are based on Hilbertian approach and Bernstein type inequalities for dependent Hilbertian random vectors.